Study on mechanical properties of mortars containing steel shot and sea sand as fine aggregate replacement. Issue 1 (March 2021) - Cabrera, H; Daza, C; Pacheco-Bustos, C; Murillo, M
Abstract: In this study, the use of solid waste known in the metallurgical market as steel shot that is generated in the production of metallic elements has been analyzed. Normally the destination of this solid waste is the sanitary landfills of the cities or the security cells since it is classified as hazardous waste. In addition, the use of materials with high availability and that were not previously used in the construction industry, such as sea sand was used in the manufacture of mortar cubes as a fine aggregate. A granulometric analysis of each of the filling materials followed by the casting of 63 mortar cubes with four different fine aggregate replacement ratios (0%, 30%, 70% and 100%) were carried out. After the curing period, the compressive strength and the weight of the resulting mortars have been determined. The results from this study indicated that by completely replacing the fine aggregate with the steel shot waste the density and the compressive strength of the resulting mortars were increased, which indicates that this new material can be used in the construction industry.